Solve for m 9+m/6=-3

Math
9+m6=-3
Move all terms not containing m to the right side of the equation.
Tap for more steps…
Subtract 9 from both sides of the equation.
m6=-3-9
Subtract 9 from -3.
m6=-12
m6=-12
Multiply both sides of the equation by 6.
6⋅m6=6⋅-12
Simplify both sides of the equation.
Tap for more steps…
Cancel the common factor of 6.
Tap for more steps…
Cancel the common factor.
6⋅m6=6⋅-12
Rewrite the expression.
m=6⋅-12
m=6⋅-12
Multiply 6 by -12.
m=-72
m=-72
Solve for m 9+m/6=-3

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top